A high gain modified SEPIC DC-to-DC boost converter for renewable energy application - Maroti P.K.; Padmanaban S.; Bhaskar M.S.; Blaabjerg F.; Siano P.; Fedk V.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inverters; Energy conversion; Gain measurement; MATLAB; Coupled inductor; DC-to-DC converters; High gain; Matrix Laboratories; Modified SEPIC; Renewable energies; Renewable energy applications; Single ended primary inductance converters (SEPIC); DC-DC converters